A BIBLIOMETRIC ANALYSIS OF GREEN PRODUCTIVITY CONCEPT - Koc, Erdinc; Şimşek, Ahmed İhsan (Sakarya University, 2021)
Aim: This study aims to determine the relationships between studies, important sub-topics and new trends in the field, in parallel with the increasing studies in the field of green productivity in recent years. Method: Using the Web of Science database, 118 studies on green productivity published between 1980 and 2021 were analyzed with bibliometric analyzes through the R and Vosviewer program. Findings: The results obtained from the analyzes were shared under two separate headings: Descriptive Statistics and Network Analysis. As descriptive statistics, the most productive journals, authors, and countries were shared. With descriptive statistics, it was found out that the most productive journal is the Journal of Cleaner Production and the most productive institution is Xiamen University. The study found that China is the most productive country in the field of green productivity. As part of the network analysis, co-occurrence, co-citation, co-authorship, and country collaboration in the field of green productivity were tried to be revealed. Co-occurrence analysis shows that 21 nodes and six clusters are formed. The authors are divided into seven clusters in the co-authorship analysis, and Li Ke has the most links. The country with the most links in the country collaboration analysis is China. In the co-citation analysis, it is seen that the studies in the field of “green productivity” are divided into three clusters. Results: As a field of study, green productivity attracts the attention of different science and social sciences disciplines, and the number of publications on this subject is constantly increasing. The interest of different disciplines in the subject field has enabled different keywords to take part in the studies. In addition to showing trends in the field, the study results also show productivity in the corresponding years’ range. With our study, researchers who want to work in the field of Green Productivity will be able to identify the guiding articles. Besides, they will be able to identify pioneering researchers, institutions and journals and see the collaborations made on the basis of country, institution and author in the field of green productivity. In this way, researchers will have the chance to look at the field of green productivity from a broader perspective. Researchers can use this study as a roadmap for their studies.

Amaç: Yeşil verimlilik alanında son yıllarda artan çalışmalara paralel olarak yapılan çalışmalar arasındaki ilişkilerin, önemli alt konuların ve alanda yeni yönelimlerin belirlenmesi bu çalışmanın amacıdır. Yöntem: Web of Science veri tabanı kullanılarak 1980-2021 yılları arasında yayımlanmış olan yeşil verimlilik üzerine yapılan 118 çalışma, R ve Vosviewer programı aracılığıyla bibliyometrik analizlerle incelenmiştir. Bulgular: Analizlerden elde edilen sonuçlar, Tanımlayıcı İstatistikler ve Ağ Analizi olmak üzere iki ayrı başlık altında paylaşılmıştır. Tanımlayıcı istatistikler altında en verimli dergiler, yazarlar ve ülkeler paylaşılmıştır. Tanımlayıcı istatistiklerle en verimli derginin Journal of Cleaner Production ve en verimli kurumun Xiamen Üniversitesi olduğu tespit edilmiştir. Araştırma, Çin'in yeşil verimlilik alanında en üretken ülke olduğunu ortaya koymaktadır. Ağ analizi kapsamında yeşil verimlilik alanında birlikte oluşum, ortak alıntı, ortak yazarlık ve ülke iş birlikleri ortaya konulmaya çalışılmıştır. Birlikte oluşum analizi, 21 düğüm ve altı kümenin oluştuğunu göstermektedir. Ortak yazarlık analizinde, yazarlar yedi kümeye ayrılmakta ve Li Ke’nin en çok bağlantıya sahip olduğu görülmektedir. Ülke iş birliği analizinde en fazla bağlantıya sahip ülke Çin'dir. Ortak atıf analizinde “yeşil verimlilik” alanındaki çalışmaların üç kümeye ayrıldığı görülmektedir. Sonuç: Bir çalışma alanı olarak yeşil verimlilik hem fen bilimlerinde hem de sosyal bilimlerde farklı disiplinlerin ilgisini çekmekte ve bu konudaki yayınların sayısı sürekli artmaktadır. Farklı disiplinlerin konu alanına ilgi göstermesi, farklı anahtar kelimelerin çalışmalarda yer almasını sağlamıştır. Alandaki eğilimleri göstermenin yanı sıra, çalışmanın sonuçları aynı zamanda ilgili yıllar aralığında verimliliği de göstermektedir. Bu çalışma ile yeşil verimlilik alanında çalışmak isteyen araştırmacılar bu alana öncülük eden çalışmaların yanı sıra yeşil verimlilik alanında üretken olan araştırmacılar, kurumlar ve ülkeleri belirleyebilecektir. Bunun yanı sıra ülke, kurum ve yazar bazında yapılan işbirliklerini tespit edebileceklerdir. Bu sayede araştırmacılar yeşil verimlilik alanına daha geniş bir perspektiften bakma imkanı bulabileceklerdir. Yaptığımız çalışma, yeşil verimlilik alanında çalışmak isteyen araştırmacılar için bir yol haritası olarak kullanılabilecektir.
YEŞİL VERİMLİLİK KAVRAMININ BİBLİYOMETRİK ANALİZİ
Keywords: Business Administration; İşletme